Reading and Young Adults Self-Directed Learning - Aziz Moummou; Said Fathi (Mediterranean Journal of Social Sciences, 2022)
The present study investigates the role of reading literacy in promoting self-directed learning for young learners. It examines the readiness for self-directed learning of 209 young adults aged 17 to 19 years old as they transition from high school to post-secondary education. This quasi-experimental study uses action research led by five teachers to compare students’ readiness for self-directed learning with reading in two scenarios: an experimental group read in a self-directed learning environment outside classrooms and a comparison group read inside the classroom in a teacher-directed environment. It is part of a 3-year longitudinal research that observes policy discourse across multiple layers of institutional hierarchy. Quantitative analyses indicated some relationships between teacher-directed and self-directed learning in terms of increasing students reading avidity and decreasing students’ perception about their readiness for self-directed reading. The findings of this study have implications for researchers and teachers studying self-directed learning with reading for young learners. Received: 21 June 2022 / Accepted: 28 August 2022 / Published: 2 September 2022